2022
DOI: 10.21037/sci-2022-025
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events, side effects and complications in mesenchymal stromal cell-based therapies

Abstract: Numerous clinical studies have shown a wide clinical potential of mesenchymal stromal cells (MSCs) application. However, recent experience has accumulated numerous reports of adverse events and side effects associated with MSCs therapy. Furthermore, the strategies and methods of MSCs therapy did not change significantly in recent decades despite the clinical impact and awareness of potential complications.An extended understanding of limitations could lead to a wider clinical implementation of safe cell therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 107 publications
1
28
0
Order By: Relevance
“…In particular, in different preclinical human studies in which organs from deceased donors were not suitable for transplantation, it has been shown that MSCs were able to reduce IRI side effects in both lung and kidney in the setting of mechanical organ perfusion [ 60 , 61 , 66 , 67 ]. However, despite the safety of MSC treatment having been widely demonstrated for different diseases in numerous patients [ 250 ], several studies have also reported adverse events and side effects associated with MSC therapy [ 251 ]. For instance, the long-term cell culture of MSCs can lead to genetic abnormalities with consequent tumorigenic effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, in different preclinical human studies in which organs from deceased donors were not suitable for transplantation, it has been shown that MSCs were able to reduce IRI side effects in both lung and kidney in the setting of mechanical organ perfusion [ 60 , 61 , 66 , 67 ]. However, despite the safety of MSC treatment having been widely demonstrated for different diseases in numerous patients [ 250 ], several studies have also reported adverse events and side effects associated with MSC therapy [ 251 ]. For instance, the long-term cell culture of MSCs can lead to genetic abnormalities with consequent tumorigenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the long-term cell culture of MSCs can lead to genetic abnormalities with consequent tumorigenic effects. Moreover, different clinical trials reported fibrosis and thromboembolism as the most common adverse events of MSCs therapy [ 251 ]. All these problems may be avoided by exploiting the paracrine properties of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, with further development of technology, such methods can be used for intraoperative cell isolation. To be used for tissue engineering in situ, the developed methods should ensure the isolation of a sufficient number of cells in a short time, and also not adversely affect the properties of the cells for safety reasons [ 125 ]. Extremely promising methods for enhancement of cell adhesion on scaffolds are presented by a surface micro/nano-imprinted patternization and laser engraving of surfaces of the implant [ 52 , 126 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing list of clinical trials accumulated numerous reports on adverse events and side effects of cell-based therapies caused by the proinflammatory profile of MSC-secretome [ 16 ]. Being presented in various tissues, MSCs are both regulators and actors of local regeneration and immunomodulation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%